Islam and Human Capital in Historical Spain - Francesco Cinnirella; Alireza Naghavi; Giovanni Prarolo (Center for Economic Studies and ifo Institute (CESifo), 2020)
This paper studies the impact of Muslim rule on human capital development. Using a unique novel dataset containing yearly data on Muslim presence in the period 711-1492 and literacy rate in 1900 for about 7500 municipalities in Spain, we estimate the local impact of the length of Muslim rule in the medieval period on literacy rate. Our findings reveal a very robust negative relationship between length of Muslim rule and levels of human capital. This result is robust to the inclusion of other possible confounding factors such as the Reconquista and the Inquisition. We argue that the characteristics of Islamic law discouraged the formation of a strong merchant class and subsequently impeded the development of forms of local self-government. This translated into lower levels of human capital for regions longer under Muslim rule. Indeed, panel estimates on a sample of cities provide evidence that locations under Muslim domination missed out on the critical junctures of institutional changes which led to a stagnation in the accumulation of human capital.
Keywords: H75; I25; N33; O10; O30; Z12; 330; muslim rule; education; literacy; self-government; merchant class; Spain